Performance Evaluation of Routing Protocols in Wireless Sensor Networks - Wagan, Raja Asif (2012)
The growing field of information technology enhanced the capabilities of the wireless communication. The large usage of WSN in the various fields of the real world is scaling with the wide variety of roles for wireless sensor network performance is challenging tasks. The issues of performance in the wireless sensor networks in many literatures, yet more studies are being done on the performance because the user and application needs are keep increasing,to encounter the challenges of the performance issues are studied here by digging out the routing protocols performance in WSN. To conduct the study and analysis on performance of WSN protocols the there are various performance metrics used for the evaluation of performance in WSN. This study will be carried out to come up with the simulation experiments over the directed diffusion (DD) and LEACH routing protocols in terms of energy consumption, congestion and reliability in the wireless sensor networks (WSN) environment with the low power consumptions. The simulation experiments in this study are based on the reliability, delay and other constraints to compare the speed, reliability and electricity saving data communication in the wireless sensor networks (WSN). The discussion of the conducted simulation experiments describes the steps which are pertaining to the protocols and tradeoffs and complexity of the data traffic for the efficiency. The NS2 simulation is used for the simulation based experiments for performance of wireless sensor network (WSN) communications which is demonstrating the comparative effectiveness of the routing protocols in the recent concepts. The results of the simulation are lightening the ways for the minimization of the delay and enhancement in the reliability issues in wireless sensor networks (WSN).